Transition de la fécondité et diversités régionales. Le cas de la Syrie - Rana Youssef (Les Cahiers d’EMAM)
After a long period during which Syria was among countries with the highest fertility in the world, Syrian fertility has spectacularly declined since the mid-1980s. However, this decline didn’t continue, and fertility entered in the early 2000s, a phase of marginal decline or quasi-stagnation around 3.5 children per woman. This study addresses fertility transition in Syria in two parts: the first is a description and an analysis of fertility levels, trends and patterns at the national level, urban-rural and regional levels over the last three decades, and the second part explores the proximate and underlying determinants of fertility. The study allows us to better identify the factors behind the evolution of fertility in Syria and to suggest possible interpretations of it in a context of a heterogeneous population characterized by a multi-ethnic and a multi-confessional diversity.